Evaluation of the influence of location of osseointegrated implants associated with mandibular removable partial dentures - Pignatta Cunha, Ligia Del'Arco [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Verri, Fellippo Ramos [UNESP]; Pereira, Joao Antonio [UNESP] (Lippincott Williams & Wilkins, 2008)
Purpose: The aim of this research was to assess, by means of, the bi-dimensional finite element method, the best implant location in the alveolar edge, through stress distribution and support structure displacement of a distal extension removable partial denture associated with an osseointegrated implant of 10.0 x .75 mm, acting as abutment for the denture base.Methods and Materials: Five models in sagittal cut were used to represent: model A-hemi arch containing natural tooth 33 and the distal alveolar edge; model B-similar to model A, but with a conventional removable partial denture to replace the absent teeth; model C (MC)-similar to the previous one, with an implant in the distal region of the edge under the denture base; model D-similar to MC, with the implant in the central region of the edge; model E-similar to MC, with an implant in the mesial region of the edge. With the aid of the finite element program ANSYS 8.0, the models were loaded with strictly vertical forces of 50 N on each cusp tip. Displacement and von Mises Maps were plotted for visualization of results.Results: The introduction of implant diminished the tendency of intrusion of the removable partial denture in all situations. The maximum stress was observed on implant in all situations. Approximating implant in direction of support teeth was benefit for stress distribution.Conclusion: Model D presented the lowest value for maximum tendency to displacement when compared with those found in the other models; model E demonstrated better relief with regard to demand from the abutment tooth; locating the implant near of the abutment tooth influenced positively the distribution of stresses on the analyzed structures.
Keywords: removable denture; dental implants; finite element analysis; biomechanics